PENAMBAHAN INNOVATED MICROORGANISM FERTILIZER (IMF) DALAM PROSES KOMPOSTING AEROBIK - IDAA Warmadewanthi; Bieby Voijant Tangahu (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
This research with adding IMF (Innovated Microorganism Fertilizer) to accelerate a compost maturation process and influence to the compost quality. This research used an anaerobic composting with windrow composting system. The variation of IMF are 0.6, 1.2, 2 and 2.5 L/kg of waste with one control reactor. The parameter used: humidity, temperature, pH, and C/N ratio. The N, P and K was analysed to identify final quality compost. The result show, the optimum dosage was 1.2 L/kg of solid waste with time composting ± 2 weeks. A good result of compost quality from the percentage of N, P and K which valued at 3.14, 0.8 and 1.5.